Development of Biology Laboratory Equipment Work Instructions Using QR Codes as a Learning Resource for Biology Education Students - Suhailah Murtaza; Suraida Suraida; Defita Permata Sari (CV. Generasi Intelektual Digital (GEN ID), 2026)
This study aims to develop an E-atlas of laboratory equipment operation instructions, utilizing QR codes as a learning resource for biology education students. The objective is to enhance students' understanding of laboratory procedures through a mobile learning medium that integrates images, descriptions, and videos. The product was developed using the 4D model and tested for both validity and practicality. Data were collected through observations, interviews, and questionnaires involving experts, lecturers, and students. The analysis covered problem identification, student needs, curriculum alignment, and lecturer requirements. The product was designed using Canva Pro and Flip PDF Professional, ensuring compatibility with both computer and smartphone platforms. The validation results indicated very high validity, with 100% from material and media experts, and 92.5% from language experts. Practicality trials with biology education students yielded a score of 88.78%, while lecturer assessments showed a score of 96.42%. These findings demonstrate that the QR code-based electronic atlas is a valid, practical, and effective learning resource for biology laboratory activities.